Cytological and phylogenetic study of Petrocosmea hexiensis (Gesneriaceae), a new species from Chongqing, China - Qiu, Zhi-Jing; Wang, Xiao-Ling; Liu, Zheng-Yu; Yang, Jian-Fen; Zhang, Shou-Zhou (Phytotaxa, 2012)
A new species, Petrocosmea hexiensis, is described and illustrated from Hexi in the Nanchuan district of Chongqing, China. The new species is similar to Petrocosmea duclouxii, but differs mainly in having a longer corolla tube and ovate-rhombic to rhombic leaves with truncated bases. Cytological and phylogenetic studies of the new species demonstrate that it has the same chromosome number as other species of Petrocosmea and that its closest relative is P. duclouxii.